Victorian Internationalisms: Response - Keirstead, Christopher (Romanticism and Victorianism on the Net, 2007)
AbstractThe articles included in “Victorian Internationalisms” stress how attention to geopolitical contexts beyond those associated with imperialism can enrich our understanding of the Victorian engagement with the wider world. At the same time, they largely resist the temptation to recast Victorian cultural production within the often valorized rhetoric of transnationalism and cosmopolitanism. They reveal instead, for instance, the subtle ways in which national self-interest could overlap with humanitarian concerns or how British authors such as Oscar Wilde both welcomed and resisted the influence of French literature and culture. “Victorian Internationalisms” likewise draws renewed attention to the category of the “literary” itself as a discursive space perhaps uniquely suited to dramatizing the complexities of geopolitical involvement.